Percutaneous closure of ductus arteriosus with the amplatzer prosthesis. The Brazilian experience - Simões,Luiz Carlos (2001)
OBJECTIVE - To report the results of percutaneous occlusion of persistent ductus arteriosus with the Amplatzer prosthesis in 2 Brazilian cardiological centers. METHODS - From May 1998 to July 2000, 33 patients with clinical and laboratory diagnosis of persistent ductus arteriosus underwent attempts at percutaneous implantation of the Amplatzer prosthesis. The median age was 36 months (from 6 months to 38 years), and the median weight was 14kg (from 6 to 92kg). Sixteen patients (48.5%) were under 2 years of age at the time of the procedure. All patients were followed up with periodical clinical and echocardiographic evaluations to assess the presence and degree of residual shunt and possible complications, such as pseudocoarctation of the aorta and left pulmonary artery stenosis. RESULTS - The minimum diameter of the arterial ducts ranged from 2.5 to 7.0mm (mean of 4.0±1.0, median of 3.9). The rate of success for implantation of the prosthesis was 100%. Femoral pulse was lost in 1 patient. The echocardiogram revealed total closure prior to hospital discharge in 30 patients, and in the follow-up visit 3 months later in the 3 remaining patients. The mean follow-up duration was 6.4±3.4 months. All patients were clinically well, asymptomatic, and did not need medication. No patient had narrowing of the left pulmonary artery or of the aorta. No early or late embolic events occurred, nor did infectious endarteritis. A new hospital admission was not required for any patient. CONCLUSION - The Amplatzer prosthesis for persistent ductus arteriosus is safe and highly effective for occlusion of ductus arteriosus of varied diameters, including large ones in small symptomatic infants.